Previous Parent Behavior On Parenting Patterns In Elementary School Students In Meuraxa District Banda Aceh - Maria Ulfa; Nur Asiah; Henki Adisa Putra (Jurnal Anestesi, 2023)
Parenting is a technique used by parents to educate, protect, and supervise their children in the family. Balanced parenting implementation is very important for the growth and development of children. This study used a descriptive method with a community health nursing approach including the assessment, intervention, implementation, and evaluation. The study on parenting patterns of parents was carried out on an elementary school children aggregate in the Meuraxa Public Health Center area, Banda Aceh using the windshield survey, questionnaires, and interviews with program administrators, parents, teachers, and elementary school students. The assessment was carried out based on Pender's theory (Health Promotion Model/HPM). The study results showed that 104 parents (43.15%) used authoritarian parenting, 137 (56.85%) used democratic parenting, and 0 (100%) used permissive parenting. It is advised that this study be put into practice to support healthy parenting practices through the use of community nursing care processes.